The purpose of God Ephesians - Sproul, Robert Charles, 1939- (Fearn, Scotland Christian Focus, 2002)
Includes index.
Originally published in 1994 as part of the Focus on the Bible series, which see also.
Keywords: Bible. N.T. Ephesians -- commentaries